Crohn’s disease: Low-Level Laser Therapy (LLLT) as an adjuvant treatment of oral lesions - Araújo, Cíntia de Souza Alferes; Mazur, Carolina Eurich; Nardino, Vitória Maria de-Melo; Souza, Hanagleicy; Stramandinoli-Zanicotti, Roberta Targa; Campos, Mirella Lindoso Gomes; Oliveira, Edimar Rafael; Amenábar, José Miguel (Journal of Oral Diagnosis, 2019)
Classified as a chronic inflammatory bowel disease, Crohns disease (CD) has a multifactorial etiology. Individual with CD can present signs/symptoms such as abdominal pain, fever, diarrhea with a serious risk of hemorrhagic progression, weight loss, anemia and malnutrition. Extra-intestinal complications of CD such as at mouth are probable in some cases. In the mouth, it may presents ulcers, verrucous lesions, swelling of the lips, recurrent aphthous stomatitis, and predisposition to fungal, bacterial and viral infections. In view of the patient´s clinical condition, oral manifestations variable, painful symptomatology and challenge in the choice of oral lesions treatment, this study presents a case of Chron´s Disease´s oral manifestations and its management with Low-Level Laser Therapy (LLLT).